Human Herpesvirus Type 8 Variants In Kaposi’s Sarcoma Before And After AIDS Era - Tornesello, Maria Lina; Biryahwaho, Benon; Downing, Robert; Hatzakis, Angelo; Alessi, Elvio; Cusini, Marco; Ruocco, Vincenzo; Loquercio, Giovanna; Mbidde, Edward Katongole; Buonaguro, Luigi; Buonaguro, Franco M. (BioMed Central, 2010)
Human herpesvirus 8 (HHV- 8) variants have been found heterogeneously distributed among human populations living in diverse geographic regions, but their differential pathogenicity in Kaposi's sarcoma (KS) development remains controversial. The aim of the present study was to analyze variations of HHV-8 genomes in tumor biopsies collected before and in the course of HIV epidemic (1971 - 2008), from patients with classic, iatrogenic, endemic as well as epidemic KS living in Africa, Europe, and North America.
Keywords: Human Herpesvirus; Diverse Geographic Region; Direct Nucleotide Sequencing; Human Herpesvirus Type; Large Predominanc